Radiotherapy-induced gut toxicity: Involvement of matrix metalloproteinases and the intestinal microvasculature. (3rd May 2016) - Stansborough, Romany L.; Al-dasooqi, Noor; Bateman, Emma H.; Keefe, Dorothy M. K.; Gibson, Rachel J.
Abstract: Purpose To review the literature surrounding the involvement of the endothelium and matrix metalloproteinases (MMP) in radiotherapy-induced gut toxicity (RIGT) and further elucidate its complex pathobiology. Results RIGT involves damage to the gastrointestinal mucosa and is associated with diarrhoea, pain, and rectal bleeding depending on the area of exposure. The mechanisms underpinning RIGT are complex and have not yet been elucidated. Members of the MMP family, particularly MMP-2 and -9, have recently been identified as being key markers in RIGT and chemotherapy-induced gut toxicity (CIGT). Furthermore, the microvasculature has long been implicated in the development of toxicities following both chemotherapy and radiotherapy, however, the mechanisms behind this are yet to be explored. Conclusions It is proposed that matrix metalloproteinases are key regulators of endothelial mediators, and may play a key role in inducing damage to intestinal microvasculature following radiotherapy.